2009
DOI: 10.2343/geochemj.1.0019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of soil selenium as affected by geologic and pedogenic processes and its effect on ecosystem and human health

Abstract: Selenium (Se) deficiency and excess in agricultural ecosystems are related to many human health problems through the food chain and depend on the spatial variability and bioavailability of Se in soils. This paper examines the spatial variability of Se in soils as affected by geologic and pedogenic processes and its effects on rice grains, groundwater, and human health using Rugao County, Jiangsu Province, an agricultural area in Yangtze River Delta Region, which has a high level of nonagenarians, as a case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This is because Se varied largely even at a small scale in soil, high Se content and low Se content usually coexist in a city, and the research scale of this paper is still too large to show relationship between Se and longevity. Some studies at the town scale and county scale within a city have shown that climate factors is almost the same, so Se will be more significant related to longevity [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because Se varied largely even at a small scale in soil, high Se content and low Se content usually coexist in a city, and the research scale of this paper is still too large to show relationship between Se and longevity. Some studies at the town scale and county scale within a city have shown that climate factors is almost the same, so Se will be more significant related to longevity [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soil Se can be considered as total Se (T-Se) and water-soluble (WS) Se (WS-Se). Soil WS-Se is a better indicator of environmental effects than T-Se [ 28 ]. In this study, both T-Se and WS-Se content of soil were considered.…”
Section: Methodsmentioning
confidence: 99%
“…In soils with low Se concentrations (<2 mg kg -1 ), the relationship between total and bioavailable selenium was roughly linear whereas in soils with total Se more than 2 mg kg -1 , there was no relationship between total and bioavailable selenium [27]. Water soluble Se is a better indicator of Se deficiency or toxicity than total Se in the soil [107]. Total concentrations do not give an adequate representation of environmental impact of Se because of its partitioning on solid phases within the soil.…”
Section: Total Selenium and Plant Bioavailable Selenium In Soilsmentioning
confidence: 95%
“…The occurrence of different chemical Se species in soil is related to pH, redox potential, and other soil solution properties including ionic strength and concentration of dissolved organic matter controlled by soil mineralogy and soil microbial activities. The water-soluble fractions of Se in soils play an important role in the biogeochemical cycling of Se in ecosystems and are the best indicators of Se deficiency or excess in soils (Sun et al, 2009). The oxidized forms of Se, selenate Se( VI), and selenite/hydroselenite Se(IV), are water soluble and hence more mobile and bioavailable.…”
mentioning
confidence: 99%